Interoperability Evaluation of BIM Data Transfer from Autodesk Revit to Robot Structural Analysis - Putu Egges Widiadnyana; I Gusti Agung Adnyana Putera; Anak Agung Gde Agung Yana (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The implementation of Building Information Modeling (BIM) in the construction industry demands efficient information integration across different disciplines. The integration between structural models and finite element models (BIM-to-FEM) has become crucial for data integration in structural analysis and modeling. The workflow from modeling to integration has a significant impact on the quality of the model output. This study aims to evaluate the level of interoperability in one-way data exchange from Autodesk Revit to Autodesk Robot Structural Analysis Professional (RSA) using the native API (Application Programming Interface) integration method. Testing was conducted through a case study involving the modeling of a multistory reinforced concrete building, with test parameters encompassing geometric consistency, material and section properties, structural connectivity, loading information, boundary conditions, and data loss. The evaluation results indicate that all data exchange indicators were fundamentally transferred successfully, achieving a 100% parameter accuracy rate. Nevertheless, this workflow does not run fully automatically and still requires significant manual adjustments and rework related to structural engineering logic. This study formulates standardized preprocessing steps to minimize misinterpretation errors before structural analysis computation is executed.